Effect of exogenous proline in two sugarcane genotypes grown in vitro under salt stress (2015)
Sugarcane (Saccharum officinarum L.) production is influenced by various abiotic stresses, including salt stress. Salinity can induce oxidative stress, which in turn damages biomolecules and cellular structures. However, such damage can be avoided or minimized by the enzymatic and non-enzymatic defense systems of plants. The aim of the study was to determine the effect of exogenous proline on Na+ and K+ content and on the activity of catalase, ascorbate peroxidase and peroxidase in two sugarcane genotypes (RB931011 and RB872552) grown in vitro under salt stress. The plants were grown for 20 days with or without 100 mM NaCl and exposed to 20 mM proline for varying period of time. The data were subjected to ANOVA factorial (two genotypes and five treatments), and the mean values were compared by Tukey test at a 5% probability. Under salinity stress, both genotypes exhibited membrane integrity reduction, reduced total soluble protein content and unaltered or increased endogenous proline content. Exogenous proline reduced Na+ accumulation in a manner proportional to the exposition period at the amino acid. In both genotypes, antioxidant enzymes activity increased with the addition of NaCl. In conclusion, RB931011 genotype showed higher proline accumulation and increased in activity of the antioxidant enzymes, indicating better salt stress tolerance than in RB872552 genotype.RESUMENLa producción de caña de azúcar (Saccharum officinarum L.) está influenciada por varios factores abióticos desfavorables, como el estrés salino. La salinidad puede inducir el estrés oxidativo, que causa daño a las biomoléculas y las estructuras celulares. Sin embargo, estos daños se puede evitar o minimizar por los sistemas de defensa enzimático y no enzimáticos de las plantas. El objetivo del estudio fue determinar el efecto de la prolina exógena en el contenido de Na+ e K+, y la actividad de la catalasa, ascorbato peroxidasa y peroxidasa en dos genotipos de caña de azúcar (RB931011 y RB872552) cultivados in vitro bajo estrés salino. Las plantas se cultivaron durante 20 días en presencia o ausencia de NaCl 100 mM y expuestos a prolina 20 mM durante un periodo de tiempo variable. Los datos fueron sometidos a ANOVA factorial (dos genotipos y cinco tratamientos), y las medias se compararon mediante la prueba de Tukey al 5 % de probabilidad. Bajo estrés salino, ambos genotipos mostraron reducción en la integridad de la membrana, disminución de las proteínas solubles totales y el mantenimiento o incremento en el contenido de prolina endógena. La prolina exógena reduce la acumulación de Na+ en proporción al período de exposición al aminoácido. En ambos genotipos, la actividad de las enzimas antioxidantes se incrementó con la adición de NaCl. En conclusión, el genotipo RB931011 mostró mayor acumulación de prolina y un mayor aumento de la actividad de la catalasa, ascorbato peroxidasa y peroxidasa, lo que indica una mejor tolerancia al estrés salino en comparación con el genotipo RB872552.